Cumulative Antibiogram: A Rapid Method to Hinder Transmission of Resistant Bacteria to Oral Cavity of Newborn Babies - Mădălina Adriana Malița; Loredana Sabina Cornelia Manolescu; Cristina Florentina Pîrvu; Radu Catalin Costea; Elena Cristina Marcov; Mihai Burlibasa; Daniela Aurelia Pîrvu; Liliana Burlibașa; Mihaela Corina Radu; Irina Prasacu; Viorel Ștefan Perieanu (MDPI AG, 2023)
Background: A rapid bacterial diagnostic is needed more and more in the treatment of patients, because of the emergence of antibiotic resistance. The cumulative antibiogram, an annual report that monitors antimicrobial resistance trends in health care facilities, may provide a profile of empirical therapy useful in diverse emergency situations, such as transmission of resistant bacteria to oral cavity of newborn babies. We aimed to draw a profile of antibiotic resistance encountered. Methods: We assessed the antibiotic resistance (ABR) profile in childbearing women and newborn babies in Ploiesti Obstetrics and Gynecology Hospital by the disk diffusion method characterizing the multidrug-resistant organisms after isolation and identification by phenotypic tests. Extended-spectrum β-lactamase (ESBL)-producing Enterobacterales (ESBL-E), Carbapenem-resistant Enterobacterales (CRE), vancomycin-resistant Enterococci (VRE), methicillin-resistant Staphylococcus aureus (MRSA) and vancomycin resistant Group B Streptococcus (VR-GBS) were detected. Results: The prevalence of antibiotic resistance was 11.32% (53/468), while the prevalence of the ESBL-E, MRSA, VRE and VR-GBS strains was 8.34% (39/468). Within the bacteria isolated from fifty-three childbearing women, the prevalence of ESBL-E, MRSA, VRE and VR-GBS was 22.64% (12/53), 32.08% (17/53), 11.32% (6/53) and 7.55% (4/53). In the whole studied group, the prevalence was 2.56% (12/468), 3.63% (17/468), 1.28% (6/468) and 0.86% (4/468). Resistant bacteria were detected at birth in the oral cavity of the newborn babies in all cases. Maternal and neonatal isolates shared similar characteristics. Conclusions: Cumulative antibiogram is useful in case of empiric treatment needed in diverse emergencies, such as transmission of resistant bacteria to oral cavity of newborn babies.